2014
DOI: 10.1308/003588414x13946184900840
|View full text |Cite
|
Sign up to set email alerts
|

Use of the surgical Apgar score to guide postoperative care

Abstract: This pilot study found that a future RCT to investigate the effect of using the SAS in a decisive approach may demonstrate a difference in postoperative care. However, significant changes to the design are needed if differences in clinical outcome are to be achieved reliably. These would include a wider array of postoperative interventions implemented using a quality improvement approach in a stepped wedge cluster design with blinded collection of outcome data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 29 publications
1
21
0
2
Order By: Relevance
“…Risk scores such as the Surgical Apgar score describe the surgical complexity and the patient's intraoperative response to surgical stress . Whether the score is useful in guiding post‐operative care and triage to the ICU needs to be clarified . Recently, two large cohort studies reported no survival benefit from ICU treatment after surgery .…”
Section: Discussionmentioning
confidence: 99%
“…Risk scores such as the Surgical Apgar score describe the surgical complexity and the patient's intraoperative response to surgical stress . Whether the score is useful in guiding post‐operative care and triage to the ICU needs to be clarified . Recently, two large cohort studies reported no survival benefit from ICU treatment after surgery .…”
Section: Discussionmentioning
confidence: 99%
“…Out of the 11 prospective studies, one study that analyzed patients undergoing orthopedic surgeries suggested that SAS could not predict adverse surgical outcomes. Haddow et al 39 analyzed 143 general and vascular surgical patients, and suggested conducting a randomized control trial due to the few cases, which provided inconclusive data. Thorn et al 47 found that general and vascular surgery patients with a lower SAS correlated well with postoperative outcomes.…”
Section: Application Of Sas By Other Researchers In Other Surgeriesmentioning
confidence: 99%
“…The surgical apgar score (SAS) has a strong correlation with the occurrence of major complications or death within 30-d following general and vascular surgery[1-4]. The scoring system is based on three intraoperative variables: Lowest mean arterial pressure, lowest heart rate and estimated intraoperative blood loss.…”
Section: Introductionmentioning
confidence: 99%